Analisis Masuknya Air Pendingin kedalam Cylinder Main Engine di Kapal MT. Transko Bima - Rodhi, Alex Bima; Darmana, Eka; Pujiyanto, Fajar (Marine Science and Technology Journal, 2025)
Ships are water transportation tools used in the sea, rivers, or lakes for various purposes such as transporting goods, passengers, and fishing. Ships generally use power from engines, such as diesel engines to drive the propellers that propel the ship in the water. The problem experienced by the author when carrying out sea practice for one year (July 2023 - July 2024), on the main engine of the MT. Transko Bima ship is the entry of coolant into the cylinder, which can have a negative impact on the performance of the main engine. Therefore, this study aims to analyze the causes of the entry of coolant into the main engine cylinder on the MT. Transko Bima ship. The research method used is a case study with a descriptive qualitative approach. Data were obtained through direct observation, interviews with engine crews, literature studies and documentation during sea practice on the MT. Transko Bima ship. The results of the study showed that damage to the exhaust valve seat was the main cause of the entry of coolant into the cylinder. This problem has an impact on the engine experiencing corrosion, water hammer, and can cause further damage if not handled immediately. Repair efforts include replacing damaged components and routine maintenance of the cooling system to prevent overheating. This research is expected to contribute to ship engine crews in handling similar problems and improving the reliability of ship operations.